2011
DOI: 10.1074/jbc.m111.290841
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Shear Stress and Sphingosine 1-Phosphate Activate Calpain to Promote Membrane Type 1 Matrix Metalloproteinase (MT1-MMP) Membrane Translocation and Endothelial Invasion into Three-dimensional Collagen Matrices

Abstract: Background: Wall shear stress (WSS) and sphingosine 1-phosphate (S1P) combine to promote endothelial sprouting and angiogenesis. Results: WSS and S1P activate calpains, and calpains are required for endothelial sprouting. Blocking calpains reduced membrane type-1 matrix metalloproteinase (MT1-MMP) membrane localization. Conclusion: Calpains regulate MT1-MMP membrane localization. Significance: These data uncover a new mechanism for controlling a key metalloproteinase in angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 62 publications
8
54
1
2
Order By: Relevance
“…Others have shown a role for mechanical regulation over MMP activity and invadopodia, which locally degrade ECM [10,11,12,32,33]. In addition, MMP-14 is known to cleave and activate MMP-2 [1].…”
Section: Resultsmentioning
confidence: 99%
“…Others have shown a role for mechanical regulation over MMP activity and invadopodia, which locally degrade ECM [10,11,12,32,33]. In addition, MMP-14 is known to cleave and activate MMP-2 [1].…”
Section: Resultsmentioning
confidence: 99%
“…Previous cell-based experiments suggested that calpain proteolyzes focal adhesion proteins, 19 thereby facilitating cell motility 11 and subsequent angiogenic responses in ECs. 10,11 Present cancer allograft experiments suggested that EC-specific introduction of CAST exhibited reduction in vascular leakage, promotion of pericyte coverage, and formation of basement membrane in tumor neovessels, as well as had angiostatic effects (Figure 2). Similarly, the absence of pericyte coverage and the formation of vascular tufts in OIR lesions were abrogated by CAST introduction (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations disclosed that calpain, a Ca 2+ -sensitive intracellular cysteine protease, exerts angiogenic effects on fluid shear stress-and VEGF-stimulated ECs based on the in vitro invasion assay 10 and in vitro tube formation assay, 11 respectively. Well-established ubiquitous isozymes, μ-and m-calpain, which require micromolar and millimolar levels of Ca 2+ for half-maximal activation, respectively, are normally kept inactive because an endogenous inhibitor, calpastatin (CAST), colocalizes and robustly downregulates their enzymatic activity intracellularly.…”
mentioning
confidence: 99%
“…1 and Table 1). It is likely that VEGF 35,36) and fluid shear stress 13,37,38) are representative activators of calpain systems in ECs under physiological conditions. ECs exhibit measurable calpain activity even under unstimulated conditions 39,40) , which may be due to spontaneous Ca 2+ mobilization in the cells 41) .…”
Section: Calpain and Vascular Integritymentioning
confidence: 99%
“…Mechanistically, calpainmediated regulation of small GTPases 13,40) as well as calpain-induced proteolysis of focal adhesion proteins 37) during EC dynamics has been documented previously. Accordingly, calpain systems appear to play key roles in angiogenesis 36,38) , wound closure 39) and maintenance of barrier functions 13,40) in ECs. In addition to motility responses, it has been reported that nitric oxide (NO) production in ECs is modulated through calpain-induced proteolysis of HSP90 42) or calpain-regulated PI3K/AMPK signaling 35) .…”
Section: Calpain and Vascular Integritymentioning
confidence: 99%